2020
DOI: 10.1002/cdq.12220
|View full text |Cite
|
Sign up to set email alerts
|

Big Five Personality Traits and Ambiguity Management in Career Decision‐Making

Abstract: Although ambiguity aversion has been found to impede the process and outcome of career decision-making, knowledge regarding the association between personality characteristics and ambiguity aversion is limited. Thus, the author examined the prediction of the Big Five personality traits for ambiguity aversion and the mediation of tolerance and confidence in ambiguity management. The results obtained with a U.S. sample (N = 239) revealed the following: (a) neuroticism positively predicted ambiguity aversion; (b)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 56 publications
2
6
0
1
Order By: Relevance
“…Although the current results resonate with previous research showing little association between SES and ambiguity aversion (Xu, 2020a), this finding should not be interpreted as evidence against the role of SES in career decision-making. In fact, the current study does indicates that childhood poverty (a key aspect of SES) positively predicts lack of readiness, which is marked by low career decision-making self-efficacy (Brown et al, 2012; Xu & Bhang, 2019).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Although the current results resonate with previous research showing little association between SES and ambiguity aversion (Xu, 2020a), this finding should not be interpreted as evidence against the role of SES in career decision-making. In fact, the current study does indicates that childhood poverty (a key aspect of SES) positively predicts lack of readiness, which is marked by low career decision-making self-efficacy (Brown et al, 2012; Xu & Bhang, 2019).…”
Section: Discussionsupporting
confidence: 58%
“…However, this area of knowledge is particularly important for career interventions that focus on reducing ambiguity aversion. Therefore, Xu and colleagues examined the predictions of calling and Big Five personality traits for ambiguity aversion and found that search for calling and neuroticism were positively associated with ambiguity aversion (Xu, 2020a; Xu & Tracey, 2017a). However, one could argue that search for calling might reflect a coping response to ambiguity aversion, while personality traits are usually not the direct intervention focus; therefore, the formative mechanism of ambiguity aversion that is malleable for clinical purposes remains remarkably unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Early research on career decision-making was based on the hypothesis of "complete rationality" in economics, following the "normative model", and emphasized the importance of cognitive factors in decision-making [40]. However, more studies have shown that individuals do not always use rational steps in the decision-making process, but are affected by personality factors [41,42]. Previous studies on the influence of personality on career decision-making difficulties have found that some personality variables related to self-perception and self-evaluation (how people view themselves) affect individual career decision-making [43].…”
Section: Core Self-evaluation and Career Decision-making Difficultiesmentioning
confidence: 99%
“…For example, inducing a transient state of sadness or anxiety can shift a subject's willingness to perform a risky decision (Raghunathan & Pham, 1999) or boost the accuracy of confidence judgments (Massoni, 2014). On a longer time scale, personality traits also affect meta-cognitive judgments (H. Xu, 2020), while metacognitive impairments and emotional dysregulation are associated in various psychiatric disorders (Rouault et al, 2018). In particular, these disorders lead to an unbalanced sense of self-confidence (or simply confidence), which refers to our capacity to perform and report robust evaluations of our decisions, and use these evaluations to control our decision-making (Yeung & Summerfield, 2012).…”
Section: Introductionmentioning
confidence: 99%